Integrated histopathological, Microbiological and hematological Assessment of Sepsis: Patterns and Correlations in a Hospital-Based Study - Sarah Riaz, Maliha Saad, Kiran Fatima, Ayesha Sajjad, Maimoona Aslam, Ahsan ul Haq (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Integrated histopathological, microbiological, and hematological assessment of sepsisin hospital settings yields critical insights into disease mechanisms. In this experimental study, comprehensive tissue biopsy